KORELASI KAPASITAS VITAL PARU DENGAN VARIABILITAS DENYUT JANTUNG MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS JENDERAL SOEDIRMAN - Abdullah, Rizky; Mustofa, Mustofa; Rahmawati, Indah (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
The prevalence of cardiovascular disease in Central Java is high and the heart rate variability (HRV) among medical students is low. Heart rate variability is a non-invasive marker that describes the balance of the autonomic nervous system in the cardiovascular system. Heart rate variability is influenced by several factors. One of the factors that affect HRV is lung function. There is synchronization between the respiratory and cardiovascular systems. However, there is not much of explanation about the correlation between Force Vital Capacity and HRV. This Study aims to determine the correlation of FVC and HRV in female students of FK Universitas Jenderal Soedirman. This study is an analytic observational study with cross sectional approach. The number of subjects in this study were 31 female students who were determined by the consecutive sampling method. Force Vital Capacity was measured by using a spirometer. Heart rate variability measurement was done using a POLAR M400 heart rate monitor connected to the Welltory application by measuring the HRV parameter in the form of SDNN (standard deviation of normal to normal). Force Vital Capacity of respondents was in the range 1.82 – 3.47 Liters and had a mean of 2,722.72 ± 0.42 L. Mean HRV (SDNN) was 57.72 ± 23.77 ms. Bivariate analysis used Pearson's correlative parametric test. The results of the Pearson correlation test between FVC and SDNN showed a value of r = 0.282 and p = 0.124. There is no correlation between heart rate variability and vital lung capacity.